2015
DOI: 10.1097/iae.0000000000000499
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Results of Polypoidal Choroidal Vasculopathy Treated With Photodynamic Therapy

Abstract: The visual outcome in eyes with PCV was stable until 2 years, but the outcome at 3 years worsened, particularly in eyes that experienced recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 63 publications
1
47
0
6
Order By: Relevance
“…Additionally, Unlike PDT, PUT do not require the injection of exogenous agents. Therefore, most of the conditions that can be treated by PDT and laser ablation, including superficial tumors such as head and neck cancer59, melanoma60, and capillary malformation such as port-wine stain61, and retinal diseases such as polypoidal choroidal vasculopathy, choroidal neovascularization, and central serous chorioretinopathy62, could potentially benefit from the development and application of PUT. In addition, current clinical applications which involve focal laser therapy of the macula, such as diabetic macular edema and branch retinal vein occlusions, would be other potential clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Unlike PDT, PUT do not require the injection of exogenous agents. Therefore, most of the conditions that can be treated by PDT and laser ablation, including superficial tumors such as head and neck cancer59, melanoma60, and capillary malformation such as port-wine stain61, and retinal diseases such as polypoidal choroidal vasculopathy, choroidal neovascularization, and central serous chorioretinopathy62, could potentially benefit from the development and application of PUT. In addition, current clinical applications which involve focal laser therapy of the macula, such as diabetic macular edema and branch retinal vein occlusions, would be other potential clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…on the long-term visual outcome of PCV treated PDT, visual acuity deteriorated at the 3-year mark. (85) Two prospective studies (3- and 5-year follow-up) have demonstrated similar results. (96,97) Adverse events with PDT include sub-retinal hemorrhage, choroidal ischemia, RPE tears and microrips at the margin of the PED, and massive-suprachoroidal hemorrhage.…”
Section: Management Of Pcvmentioning
confidence: 68%
“…(84,85) Younger age, smaller lesion size, better baseline vision, and less baseline hemorrhage, are predictive measures of favorable one year visual outcomes following PDT monotherapy. (86) Numerous studies have evaluated PDT monotherapy for short and mid-term results and concluded that visual acuity remains stable or improved, while polyp regression occurs in 80–95% of treated eyes.…”
Section: Management Of Pcvmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, PDT is widely regarded as effective in the treatment of PCV due to the regression of polyp‐like dilations in spite of the relative lack of visual improvement within 2 years . Wong et al also reported that the visual outcome in eyes with PCV was stable until 2 years, while the outcome at 3 years worsened, particularly in eyes that experienced recurrence.…”
Section: Introductionmentioning
confidence: 99%